TOOMPEA HILL STABILITY AND TALLINN AREA SUBSIDENCE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1999)
This paper analyses the deformation of the Toompea Hill, using the theoretical and numerical modeling. Analysis showed that the Toompea Hill deformation is connected with the subsidence of the territory of Tallinn. Numerical modeling, using one? dimensional model and FLAC-program evaluated the calculations. Total deformations of the layers and surface subsidence are quite small and do not exceed 7 mm, owen to the consolidated Vendian sandstone and clays.